Rectifier systems for variable speed wind generation : a review - Jayasinghe, S. D. Gamini. (2013)
The drive towards high efficiency wind energy conversion systems has resulted in almost all the modern wind turbines to operate in the variable speed mode which inevitably requires back-to-back power electronic converters to decouple generator dynamics from the grid. The aim of this paper is to present an analysis on suitable topologies for the generator-side converter (rectifier) of the back-to-back converter arrangement. Performance of the two most popular rectifier systems, namely, the passive diode bridge rectifier and the active six-switch two-level rectifier are taken as two extremes to evaluate other topologies presented in this paper. The other rectifier systems considered in this study include combinations of a diode bridge rectifier and electronic reactance(s), a combination of a rectifier and a dc-dc converter and a half controlled rectifier. Diode-clamped and capacitor-clamped three-level active rectifier topologies and their possible switch reductions are also discussed in relation to the requirements of modern high power wind energy conversion systems (WECSs). Simulation results are presented to support conclusion derived from this analysis.